Stress adaptation has a minor impact on the effectivity of Non-Thermal Atmospheric Plasma (NTAP) against Salmonella spp. (December 2017) - Calvo, Tamara; Alvarez-Ordóñez, Avelino; Prieto, Miguel; Bernardo, Ana; López, Mercedes
Abstract: This study was aimed at studying the influence of gas composition (air and nitrogen) at different flow rates (5, 10 and 15 Lm − 1 ) and stress adaptation (growth under a wide range of temperatures [10–45 °C] and acid conditions [up to pH 4.5, using different organic acids] or short-term exposure to acid, cold or heat stress shocks) on the inactivation by Non-Thermal Atmospheric Plasma (NTAP) of S. Typhimurium CECT 443 and S. Enteritidis CECT 4300. Results obtained evidence that microbial inactivation was significantly higher when air was used for NTAP treatments. D-values obtained using air ranged from 0.86 to 2.43 min and 0.90 to 1.69 min for S. Typhimurium and S. Enteritidis, respectively, while those obtained using nitrogen ranged from 3.08 to 5.75 min and 2.28 to 5.54 min, respectively. Microbial inactivation also increased with increasing flow rates, although differences were not statistically significant in all cases. Growth temperature and pH or exposure to acid, cold or heat stress shocks had a minor impact on NTAP resistance. Indeed, D-values obtained under the different stress adaptation scenarios were not significantly different from those obtained for non-adapted control cultures (1.38 ± 0.39 for S. Typhimurium and 1.23 ± 0.36 for S. Enteritidis), with the exception of cells grown at 10 °C, which were significantly more sensitive to NTAP, with D-values of 0.68 ± 0.11 and 0.45 ± 0.10 min, respectively, for S. Typhimurium and S. Enteritidis. These findings suggest that adaptive responses triggered by exposure to acid, cold or heat stresses, already described in the past for these two Salmonella strains, do not provide protection against NTAP treatments, which allows us to conclude that NTAP may be a first-choice technology to be included into food processing schemes following a hurdles technology approach in combination with acidification, mild heating or refrigeration. Graphical abstract: Highlights: The effectiveness of plasma treatments against S. Typhimurium and S. Enteritidis was assessed. Sensitivity to plasma was higher when air instead of nitrogen was used. Stress adaptation had a minor impact on plasma resistance. Growth at low temperature (10 °C) enhanced the effectiveness of plasma.